A novel method of transvesicoscopic ureteral reimplantation of an ectopic ureter with a mate ureter in a duplex kidney. Issue 2 (19th November 2021) - Nishio, Hidenori; Mizuno, Kentaro; Matsumoto, Daisuke; Kato, Taiki; Kamisawa, Hideyuki; Kurokawa, Satoshi; Nakane, Akihiro; Maruyama, Tetsuji; Yasui, Takahiro; Hayashi, Yutaro
Abstract : Introduction: The reimplantation of an ectopic ureter is still performed as an open surgery, although laparoscopic or robot‐assisted laparoscopic surgery has gained popularity as a minimally invasive treatment for pediatric urological disorders. Case presentation: A 15‐day‐old Japanese boy was referred to our hospital with right hydronephrosis. A detailed examination revealed complete ureteral duplication on the right side and a dilated ectopic upper pole ureter, opening into the prostatic urethra. Since the patient had recurrent febrile urinary tract infections, we performed plication and ureteral reimplantation of the dilated ectopic ureter using a transvesicoscopic surgical method at the age of 2 years and 5 months. Conclusion: We safely performed transvesicoscopic ureteral reimplantation for an ectopic upper pole ureter with a mate ureter in a duplex kidney, following the detection of an ectopic ureter within the bladder, due to the prior understanding of the wrapping of both ureters in a common sheath.